Hereditary Motor Sensory Neuropathy with Pyramidal Signs-Report of a rare case. - Sasidharan, Aswathy; Pranaav, Arun S.; Ghafoor, P A Fazal (Nepal Journal of Neuroscience, 2024)
Introduction: Hereditary motor and sensory neuropathy is a chronic degenerative disorder of the peripheral nerves. It has neuropathic pattern of motor and sensory deficits without evidence of Upper motor neuron signs such as spasticity, brisk deep tendon reflexes. Material and Methods: We report a case of 19 year old male having above mentioned features of neuropathy and pyramidal signs combined. We also have done literature search to find similar case reports. Results: There were 10 articles including ours having cases presenting with neuropathy and pyramidal tract signs. Genetic mutations were mentioned in 5 articles. Our patient had heterozygous deletions encompassing COX 10 and PMP22 gene mutation. Spasticity was mentioned in three out of ten. Flexor plantar response was seen in four out of ten including our case. Conclusion: HMSN may have unusual presentation like spasticity, brisk deep tendon reflexes, extensor plantar response. Neurophysicians should also be aware of the variety of differentials that have such presentation. The clinical clue to diagnosis is the presence of foot deformities, chronic indolent course of illness. Genetic analysis is usually confirmatory